Climate Change : A Global Phenomena - Archana (SCHOOL SCIENCE, 2017)
Increasing world population and the increasing desire of human beings to raise their standard of living has led to technological innovations of all kinds. These innovations have made life more comfortable but at the cost of increased demands for food, air, water, minerals and energy. Rapid depletion of natural resources all around us has caused unprecedented changes in global climate resulting in serious implications on the survival of both human and animal species on earth. It is feared that one-fourth of earth’s species could be headed for extinction by 2050. We should emphasise to use renewable sources of energy like wind, solar, biomass and ocean geothermal energy